Legal Problematics in the Field of Civil Aviation Between Federal Governorment and Kurdistan Region - األسخاذ امىساعد امدكخِر َيِا إةراَيه قادر (QALAAI ZANIST SCIENTIFIC JOURNAL, 2018)
Recently the problem of civil aviation authority in Iraq as a federal state has emerged, especially after the decision of Iraqi Civil Aviation Authority to ban international flights at the international airports of Erbil and Sulaymaniyah from 29 September 2017. This research is a study for the legal dimension of this issue with a view to determining the competent authority for the organization of civil aviation in Iraq in accordance with the provisions of the Iraqi constitution of 200 and the civil aviation legislation in Iraq. We concluded that the competent authority for civil aviation in the Kurdistan Region is the authorities of the Region itself and not the federal authorities, and the decision of the Civil Aviation Authority of Iraq to suspend all international flights to Erbil and Sulaymaniyah international airports contrary to the provisions of the Constitution and the in force laws in Iraq. We recommended the Iraqi legislator to amend the Iraqi Civil Aviation Law No. (148) for the year 1974, in light of the provisions of the Iraqi constitution (2005), or enactment a new civil aviation law in Iraq, also we recommend the Kuridstan Parliament to enact the Civil Aviation Law in the Kurdistan Region based on the provisions of Article (115) and (121/II) of the Iraqi Constitution (2005).